دور المؤسسات الناشئة في تحقيق التنمية المستدامة -حالة الجزائر- - بوطرفة, صورية; نصرة, نجوى (جامعة الوادي - University of Eloued, 2022)
Startups are Algeria's its ideal choice for economic diversification and economic dependence elimination. It have become the most important mechanism and the best tool for achieving sustainable development, which imposes on Algeria, through the application of the new economic model, to direct attention towards it and work to promote it and increase its effectiveness. This is with the aim of achieving development programs efficiently and encountering obstacles and challenges facing the sustainable development process. In this research paper, this will be clarified by presenting the case of Algeria
The Role of Startups in Achieving Sustainable Development: Algeria as a Case Study
مقال
Keywords: المؤسسات الناشئة ; التنمية المستدامة ; التنمية ; الأنموذج الاقتصادي